BERMAIN PENCAMPURAN WARNA SEBAGAI ASPEK PERKEMBANGAN KEMAMPUAN SAINS PADA ANAK TK PRATAMA WIDYALAYA KUMARA GIRI KUSUMA KABUPATEN JEMBRANA - Wardhani, Ni Ketut Srie Kusuma; Gusti Ayu Agung Riesa Mahedradhani (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
Play is fundamental to early childhood development, offering children valuable opportunities to acquire knowledge and refine various skills. This study examines the effectiveness of color mixing play as a means to enhance science-related skills in young learners. Conducted as Classroom Action Research, it spans two cycles with 21 kindergarten students at Pratama Widyalaya Kumara Giri Kusuma in Jembrana Regency as participants. Data were collected through observation, field notes, and documents and were analyzed using descriptive statistical methods. Results indicate a substantial improvement in active learning engagement, rising from 60.93% in Cycle I (categorized as moderately active/developing) to 90.18% in Cycle II (very active/developing exceptionally well). Correspondingly, the average learning outcomes increased from 74.50 in Cycle I to 85 in Cycle II, with learning mastery rates progressing from 75.5% to 90.4%. These findings highlight that color mixing play effectively supports the development of science skills and serves as a practical, engaging educational strategy in early childhood science education. Beyond science, color mixing play supports growth in other areas, including language, cognitive, physical motor, social-emotional, moral, and artistic development. However, a primary challenge identified was limited playtime, which restricts the extent of skill development. Despite this, the findings suggest that color mixing activities can be a valuable addition to early childhood curricula, providing a fun and interactive way to promote scientific thinking and multi-faceted development in young children.